2022
DOI: 10.3389/fgene.2022.940306
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and immune-related value of complement C1Q (C1QA, C1QB, and C1QC) in skin cutaneous melanoma

Abstract: Background: Skin cutaneous melanoma (SKCM) is a common malignancy that is associated with increased morbidity and mortality. Complement C1Q is composed of C1QA, C1QB, and C1QC and is involved in the occurrence and development of many malignant tumours. However, the effect of C1QA, C1QB, and C1QC expression on tumour immunity and prognosis of cutaneous melanoma remains unclear.Methods: First, we analysed C1QA, C1QB, and C1QC expression levels and prognostic values using Gene Expression Profiling Interactive Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…The over-expression of C1QA and C1QB are protective factors to significantly prolong the survival time and the risk factors<1. In a study about skin cutaneous melanoma, the researcher found that over-expression levels of C1QA, C1QB and C1QC are protective factors which improve survival time at different stages [21] . The results obtained are consistent with our results.…”
Section: Resultsmentioning
confidence: 99%
“…The over-expression of C1QA and C1QB are protective factors to significantly prolong the survival time and the risk factors<1. In a study about skin cutaneous melanoma, the researcher found that over-expression levels of C1QA, C1QB and C1QC are protective factors which improve survival time at different stages [21] . The results obtained are consistent with our results.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, C1QB expression shows a positive correlation with predictive biomarkers for immunotherapy, such as PD-L1 expression and CD8+ T cell infiltration[24]. Furthermore, in malignant melanoma, C1QB promotes proliferation, migration and invasion, while inhibiting cell apoptosis[26], and the high-expression group exhibits significant enrichment of genes related to immune and apoptosis[21]. In our study, we found that high expression of C1QB in DLBCL was associated with a worse prognosis and positively correlated with CD8+ T cells infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…HLA class I antigen deletion caused by B2M mutation mostly occurs under the activated PDCD1 (PD-1)-positive T cell infiltration condition [ 26 ]. C1QB is the diagnostic and prognostic biomarker for skin cutaneous melanoma patients [ 27 ], IRF4 could promote melanoma cell growth via upregulating C1QB [ 28 ]. The combination of C2 and additional therapeutic mAbs, such as type II anti-CD20/CD22/CD38 samples, can overcome complement attack resistance in tumor cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%